Step-by-step explanation:
Q1 . (f+g)(x) = f(x) + g(x)
=4x-4 +2x^2 -3x
= 2x^2 + x -4
Q2. (f-g)(x) = f(x) - g(x)
= 2x^2−2 - (4x+1)
= 2x^2 -2 -4x -1
= 2x^2 - 4x -3
Q3. h(x)=3x−3 and g(x)=x^2+3
(h.g)(x) = h(x) × g(x)
= (3x-3) × (x^2 + 3)
=3x^3 -3x^2 + 9x -9
Q4.f(x)=x+4 and g(x)=x+6
(f/g)(x) = f(x) ÷ g(x)
= x+4 / x+6
the domain restriction is x>-6
x<-6
x doesn't equal (-6)
6x + 52 > 130
Subtract 52 from both sides:
6x > 78
Divide both sides by 6:
X > 78/6
X > 13
0.44
dadadadadadadadadadadadadadada
Answer:
You Can Scan This In The App And Then Its Solved
Answer:
9 yards
Step-by-step explanation:
36 divided by 4 = 9